The Patterns of Hate Speech in The Viewers' Comments Column on The Channel Youtube with The Topic of Puan Maharani In 2019 - Paramita, Tiara Pradnya; Subyantoro, Subyantoro; Pristiwati, Rahayu (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Social media in its use nowadays does not only just pack information, but also provides opportunities to produce information and disseminate information. Furthermore, social media users have the right to choose, determine, and create informative messages or points of view they want; social media may now be a part of human existence and has been consumed massively including Youtube which is one of the most popular social media platforms. However, it cannot be denied that the function of social media can be likened to a double-edged sword; on the one hand it can be used for big activities, but on the other hand it can be used for bad things and is detrimental to society. The problem in this research was "How is the form of hate speech in the viewers’ comments column of the YouTube channel on the topic of Puan Maharani in 2019?". The research design used a qualitative research design that was descriptive with research data using commentary data. This study used transcription techniques and note-taking techniques. The results showed that the highest number of utterances was 300 utterances containing hate speech, nine forms of hate speech were obtained. Of the nine forms of hate speech that were considered to be the style of speech that was widely used by the public in conveying comments on social media. The form of the utterance was a form of hate speech, as much as 96.67% of assertive speech acts.